Association between self‐reported medical diagnosis of depression and metabolic syndrome in a population‐based study: A propensity score‐matched analysis - Go‐Un Kim; Namhee Kim; Heejung Kim (Nursing Open, 2022)
Abstract The aim was to compare the metabolic syndrome in adults with and without depression in Korea using the 2013–2015 Korea National Health and Nutrition Examination Survey. A cross‐sectional study was conducted involving secondary data analysis. National survey data on the self‐reported medical diagnosis of depression and metabolic syndrome were collected between 2013 and 2015 and released for research purposes in 2017. We conducted a propensity score‐matched study that included adults (n = 494) with and without depression at a 1:1 ratio, to reduce the impact of potential confounding factors between groups. Depression was not significantly associated with changes in metabolic syndrome. However, participants with depression had significantly higher triglycerides than those without depression (p = .008), highlighting the importance of periodically checking triglycerides in depressed patients. Nurses need to check the subcomponents of metabolic syndrome in depressed patients periodically, especially regarding the management of triglycerides.